A Deceptively Simple Solution for Refractory Melasma: Glycolic Acid Peels and Hydroquinone at Home - Mashiko, Takanobu (Plast Reconstr Surg Glob Open, 2017)
Although various treatment methods for melasma have developed, substantial improvement of the condition is sometimes difficult. We have experientially found that some of refractory melasma caused by daily friction can easily be treated by using a combination of a peeling agent (20% glycolic acid) and a depigmenting agent (5% hydroquinone) twice daily at home. And here, by performing skin biopsies, we revealed the pathological mechanism: hyperkeratosis caused by repeated physical stimulus, which prevents infiltration of topical therapeutic agents, was dramatically reduced by chemical peeling, resulting that the melanin pigments were effectively cleared by topical hydroquinone.